Kimura’s disease as an uncommon cause of post auricular swelling - Bendiganahalli Venkate Gowda, Chandre Gowda; Gandham, Madhuri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Kimura’s disease (KD) is a rare chronic inflammatory disorder of unknown etiology, primarily seen in young Asian males. In India, only 200 cases have been reported worldwide since its histopathological diagnosis. The disease is characterized by painless subcutaneous swelling in head & neck region, blood and tissue eosinophilia and raised Immunoglobulin E (IgE) levels. A systematic multidisciplinary approach is mandatory to rule out the other common causes of post auricular lymphadenopathy. The diagnosis of KD can be difficult and misleading and patients with this disease are often evaluated using avoidable procedures by just not being aware of KD. Here, we present a case of a 20 year old male who presented with nodular swellings in the bilateral post auricular region. The diagnosis of KD was done based on characteristic histopathologic finding in conjunction with peripheral eosinophilia.